Study on the Fluorescence Characteristics of CdTe and Charged Coumarin-Contained Polymer Blending System - Wang, Xu; Li, Lichao; Chen, Deben; Zhong, Anyong (Asian Journal of Chemistry, 2012)
In this paper, a series of positively charged coumarin-contained polymer (C-CPA) were synthesized and a negatively charged CdTe quantum dots (CdTe QDs) protected by thioglycolic acid (TGA) was prepared. C-CPA and CdTe QDs were blended in mixed solution to build a blending system. The photoluminescent properties of both C-CPA and CdTe QDs were studied and the influence of the solvent on the size of CdTe QDs was studied as well. By controlling the proportions of the two mixtures, some regularly phenomena were found. As the proportion of CdTe QDs rising in the mixture, the fluorescence intensity of C-CPA declined; as the proportion of C-CPA rising, the fluorescence intensity of CdTe QDs rose significantly. These phenomena followed the fluorescence resonance energy transfer theory (FRET). The electrostatic force between the two mixtures caused the interaction between them. The study confirmed that an energy donor-acceptor pair was formed in this blending system.